2021
DOI: 10.1101/2021.02.04.429735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic reconstruction of ancestral ecological networks through time for pierid butterflies and their host plants

Abstract: The study of herbivorous insects underpins much of the theory that concerns the evolution of species interactions. In particular, Pieridae butterflies and their host plants have served as a model system for studying evolutionary arms-races. To learn more about how the two lineages co-evolved over time, we reconstructed ecological networks and network properties using a phylogenetic model of host-repertoire evolution. In tempo and mode, host-repertoire evolution in Pieridae is slower and more conservative when … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Furthermore, in taxa that permit it, sequencing ancestral and extant lineages within a species over time could reveal the impact of host associations on the evolutionary rate, diversification, and the genomic bases of interactions [42]. Alternatively, one could model the evolution of the host repertoire of a symbiont group [51]. Therefore, incorporating Box…”
Section: Trends Trends In In Ecology Ecology and Evolution Evolutionmentioning
confidence: 99%
“…Furthermore, in taxa that permit it, sequencing ancestral and extant lineages within a species over time could reveal the impact of host associations on the evolutionary rate, diversification, and the genomic bases of interactions [42]. Alternatively, one could model the evolution of the host repertoire of a symbiont group [51]. Therefore, incorporating Box…”
Section: Trends Trends In In Ecology Ecology and Evolution Evolutionmentioning
confidence: 99%
“…Predictions of unobserved host-parasite associations are often based on an assumption that present-day associations accurately reflect potential host ranges [31,35,36]. However, host range is a dynamic property of parasites that evolves through cospeciation, host shifts, and the gains and losses of hosts over varying timescales [37][38][39][40][41]. Changes in parasite host specificity as a result of host-switching and shifting geographic ranges have attracted considerable attention by researchers [42][43][44][45][46][47], whereas extinction history has tended to be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Few recent studies on the Stockholm paradigm have integrated network analyses (but see D'Bastiani et al 2020;Braga et al 2021). Instead, the focus has remained on inferring ancestral host-parasite interactions (Braga et al 2020(Braga et al , 2021 rather than predicting undetected links.…”
Section: Introductionmentioning
confidence: 99%
“…Few recent studies on the Stockholm paradigm have integrated network analyses (but see D'Bastiani et al 2020;Braga et al 2021). Instead, the focus has remained on inferring ancestral host-parasite interactions (Braga et al 2020(Braga et al , 2021 rather than predicting undetected links. The distinction between undetected and unrealised links remains a major hurdle for network studies as observed interactions will often present an underestimation of the real interaction diversity (Fu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation